ANALISIS PEMANFAATAN VIDEO PEMBELAJARAN DALAM MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA - Diajeng Gusti Ayu Niken Agustina; Annisya Nurlaily; Fitriyani; Silva Yuliana; Nur Diana Rubianingsih; Sutiasih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Motivation to learn is a crucial factor in students' success in mathematics education. When motivation is low, students often lose interest in the learning process, which negatively impacts their conceptual understanding and academic outcomes. Therefore, there is a need for instructional media that can create a more engaging learning atmosphere and foster active student participation; the use of instructional videos is one such approach. This article aims to examine the effectiveness of using instructional videos to enhance motivation in learning mathematics, drawing upon previously published research findings. The study employs a literature review approach, involving the search, collection, analysis, and synthesis of scholarly articles regarding the application of instructional videos in mathematics education. Data sources consist of national and international journals published within the last five years. The analysis indicates that the consistent use of instructional videos has a positive effect on increasing student learning motivation. Delivering material via video makes the learning process more engaging, helps students visualize abstract mathematical concepts, improves their focus and attention, and encourages active participation during lessons. Furthermore, instructional videos offer students the opportunity for independent learning tailored to their individual abilities and learning paces. Based on this review, it can be concluded that instructional videos are a highly effective medium for boosting motivation in mathematics learning and creating a more interactive and meaningful learning experience.